El principio del interés superior del niño - Legerén Molina, Antonio (2019)
According to the United Nations Convention on the Rights of the Child 1989, theprinciple of “best interest” must be the “primary consideration” in making decisionsconcerning every child (cfr. artículo 3 de cdn). States must implement the relevantprocedures to determine which decision corresponds in each case to such interest.Similarly, and for children in an environment of armed conflict, unhcr has developedtwo methods —“best interest assessment” and “best interest determination” (bid)— thatcan be applied when the procedures designed by the States are not available. Theseissues are discussed in this article.